The Impact of Air Pollution Exposure on Pulmonary Function Among Primary School Children in Metropolitan Areas - Alwafi, Haris (Oshada, 2026)
Urban air pollution has become a critical public health concern in metropolitan areas, particularly for children whose respiratory systems are still developing. Exposure to pollutants such as particulate matter (PM₂.₅ and PM₁₀), nitrogen dioxide (NO₂), and ozone (O₃) may impair lung growth and increase susceptibility to respiratory disorders. This study aimed to analyze the association between air pollution exposure and pulmonary function among primary school children in a metropolitan city. An analytical cross-sectional design was conducted involving 150 children aged 7–12 years from schools located in high-traffic and moderate-traffic areas. Ambient air pollutant concentrations were obtained from urban monitoring stations and school-based measurements, while pulmonary function was assessed using standardized spirometry to measure FEV₁, FVC, and FEF25–75. Data were analyzed using independent t-tests and multiple linear regression controlling for age, sex, body mass index, asthma history, and parental smoking. The results indicated significantly higher pollutant concentrations in high-traffic areas (p < 0.001) and significantly lower mean FEV₁, FVC, and FEF25–75 values among exposed children (p < 0.05). PM₂.₅ emerged as the strongest negative predictor of pulmonary function. In conclusion, urban air pollution exposure is significantly associated with decreased lung function among primary school children, highlighting the urgent need for strengthened environmental health policies and school-based preventive strategies.